Analisis Perilaku Kerja Pegawai pada Kantor Kecamatan Teluk Jambe Timur - Hasanah, Mila Ushwatun; Uus Mohammad Darul Fadli; Laras Ratu Khalida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the work behavior of employees at the East Telukjambe Sub-district Office, Karawang Regency, based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 6 of 2022. This study uses a qualitative approach with a focus on seven indicators of employee behavior, namely Service Orientation, Accountability, Competence, Harmony, Loyalty, Adaptability, and Collaboration. Informants in this study consist of the Sub-district Head, staff members, and the community. Primary data were obtained through direct interviews with respondents, while secondary data were obtained from related literature and documentation. The analysis results indicate that the East Telukjambe Sub-district Office shows positive performance in all the examined indicators of employee behavior. Measures such as clear service policies, employee training, participatory performance evaluation systems, and promotion of collaboration among employees have been taken to strengthen this performance.